Effects of Glucagon-Like Peptide-1 Receptor Agonists on Bone Metabolism in Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Xin Li; Yang Li; Chen Lei (International Journal of Endocrinology)
Background. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are an intriguing class of antihyperglycemic drugs for type 2 diabetes mellitus (T2DM). Such drugs not only play a primary role in regulating blood glucose levels but also exhibit additional pleiotropic effects, including potential impacts on bone metabolism and fracture risk. However, the mechanism of such drugs is unclear. The purpose of this study was to evaluate the effect of GLP-1 RAs on bone metabolism in T2DM. Methods. From database inception to May 1, 2023, the searches were conducted on multiple databases such as Web of Science, Embase, PubMed, CNKI, the Cochrane Library, Wanfang, and VIP. We systematically collected all randomized controlled trials of bone metabolism in patients with T2DM treated with GLP-1 RAs. The quality evaluation was performed according to the Cochrane Handbook for Systematic Reviews of Interventions. Data extraction was analyzed using Review Manager 5.4 software, and funnel plots were drawn to evaluate publication bias. Results. Twenty-six randomized controlled trials that met the inclusion criteria were included, involving a total of 2268 participants. In this study, compared to other antidiabetic drugs or placebo, GLP-1 RAs were found to significantly increase serum calcium (mean difference (MD) = 0.05, 95% confidence interval (CI) (0.01, 0.09), P=0.002], bone alkaline phosphatase [standardized MD (SMD) = 0.76, 95% CI (0.29, 1.24), and P=0.001), and osteocalcin (SMD = 2.04, 95% CI (0.99, 3.08), and P=0.0001) in T2DM. Specifically, liraglutide increased procollagen type 1 N-terminal propeptide (SMD = 0.45, 95% CI (0.01, 0.89), and P=0.04). GLP-1 RAs were also associated with a reduction in cross-linked C-terminal telopeptides of type I collagen (SMD = −0.36, 95% CI (−0.70, −0.03), and P=0.03). In additionally, GLP-1 RAs increased lumbar spine bone mineral density (BMD) (SMD = 1.04, 95% CI (0.60, 1.48), and P<0.00001) and femoral neck BMD (SMD = 1.29, 95% CI (0.36, 2.23), and P=0.007). Conclusions. GLP-1 RAs can not only improve BMD in the lumbar spine and femoral neck of patients with T2DM but also protect bone health by inhibiting bone resorption and promoting bone formation. Systematic Review Registration. PROSPERO, identifier CRD42023418166.